PENGARUH KECERDASAN EMOSIONAL DAN STRES KERJA TERHADAP KEPUASAN KERJA DAN DAMPAKNYA TERHADAP KOMITMEN ORGANISASI FRONTLINER BAKTI PT BANK CENTRAL ASIA Tbk KCU JAMBI - Emma Rachmelya; Arna Suryani (Universitas Batanghari Jambi, 2017)
The research aims to analyze the influence of emotional intelligence, job stress and job satisfaction on organizational commitment, both directly and indirectly. This research is done on Bakti Frontliner who work as teller and customer services of PT Bank Central Asia Tbk Jambi Branch, amounted at 60 people spread in nine sub branch. Technique used in sampling is census, where all of the population is used as sample. Analysis unit used is path analysis. The research result that emotional intelligence and job satisfaction influence positively and significantly on organizational commitment, while job stress influence negatively and significantly on job satisfaction and organizational commitment. Other than that emotional intelligence and job stress influence directly on organizational commitment through job satisfaction.Keywords: emotional intelligence, job stress, job satisfaction, organizational commitment